366 readings from Taoism and Confucianism/ edited by Robert Van De - "Weyer, Robert Van De (ed.)" (Mumbai, 2007)
Tao is best translated as the 'Way'; it may also be understood as the first principle from which everything comes, and to which all will return. Jaico's 366 Readings Series is the first comprehensive collection of the spiritual literature of the whole world presented in accessible form. It is aimed at people who wish to broaden their spiritual outlook, and also at the much larger group who have little or no attachment to a religious community, but seek spiritual wisdom.
Keywords: Religion-China